Pengaruh Media Pembelajaran 3D Piramida Hologram Terhadap Minat Belajar Siswa Pada Materi Vulkanisme Kelas X SMAN 54 Jakarta - Nurrahman, Farah Adhiba; Aris Munandar; Sucahyanto (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
This study aims to determine the effect of 3D Hologram Pyramid learning media on students' interest in learning about volcanism in class X at SMAN 54 Jakarta. The research method used is a quantitative approach with a quasi-experimental design, specifically a one-group pre-test post-test design. The sampling technique employed is random sampling, ensuring that all members of the population have an equal chance of being selected. The sample for this study consists of 36 students from class X-F. Data collection was conducted using a learning interest questionnaire administered before and after the treatment. The research instruments were found to be valid and reliable, and the data was determined to be normal and homogeneous. Based on the research results, the average score of the questionnaire after the treatment for the experimental class was 81%, categorized as